The Effect of Streamer Credibility on Increasing Purchase Intention in Live Streaming Shopping Skintific Indonesia - Salsabila, Sabina Alya; Riski Taufik Hidayah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of streamer credibility on purchase intention, both directly and indirectly through the mediating variable of interactivity, in the context of live streaming Skintific Indonesia products. This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques. Three constructs were tested: Streamer Credibility (SC), Interactivity (I), and Purchase Intent (PI). The validity test results showed that most indicators had outer loading values above 0.50, and the AVE values for all constructs were above the minimum threshold of 0.50, except for the Interactivity construct. However, the Composite Reliability (CR) and Cronbach's Alpha (α) values were still below 0.70, indicating weaknesses in the internal reliability of some constructs. The hypothesis testing results show that Streamer Credibility has a significant direct effect on Purchase Intent (β = 0.435; T = 10.058; p < 0.001), and Streamer Credibility also has a significant effect on Interactivity (β = 0.448; T = 10.643; p < 0.001), and Interactivity positively influences Purchase Intent (β = 0.127; T = 3.219; p = 0.001). There is an indirect effect of Streamer Credibility on Purchase Intent through Interactivity (β = 0.082; T = 3.064; p = 0.002). These findings confirm that streamer credibility plays an important role in shaping consumer purchase intention, both directly and through increased interactivity during live streaming sessions.